Factors Predictive of Retroperitoneal Lymph Node Metastasis in Endometrial Cancer - Urzal, Cecília (2014)
Introduction: It has been suggested that a complete staging may be safely omitted in endometrial carcinoma patients at low risk for lymph node metastasis. The purposes of our study were to explore the prognostic significance of pathologic factors for pelvic and paraaortic nodal spread and to validate the Mayo algorithm in order to identify patients in whom lymphadenectomy may be avoided.Material and Methods: We conducted a retrospective review including 208 patients, regarding the evaluation of pathologic variables and nodal metastases. Statistical analysis was performed using the chi-square test, the Fisher exact test and the Student’s t-test.Results: Myometrial invasion > 50% (p < 0.001), cervical invasion (p = 0.001), lymphovascular space invasion (p = 0.003) and positive peritoneal cytology (p = 0.03) were significant predictors of retroperitoneal lymph node dissemination. Pelvic lymph node metastases were predictive of positive paraaortic lymph nodes (p < 0.001).Discussion: The Mayo algorithm identified patients without pelvic or paraaortic nodal metastases with a 98.4% negative predictive value (61/62). Myometral invasion ≤ 50% and absence of cervical and lymphovascular invasion presented a negative predictive value of 98.8% (79/80).Conclusion: Although the Mayo criteria predict a very low likelihood of retroperitoneal nodal metastases, the combination of myometral invasion ≤ 50% and absence of cervical or lymphovascular invasion would have safely avoided lymphadenectomy in a larger number of women.